2013
DOI: 10.1103/physreve.87.062503
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamics of stress in clamped nematic elastomers

Abstract: We describe the complex time dependence of the buildup of force exerted by a clamped photoelastomer under illumination. Nonlinear (non-Beer) absorption leads to a bleaching wave of a significant cis isomer dye concentration deeply penetrating the solid with a highly characteristic dynamics. We fit our experimental response at one temperature to obtain material parameters. Force-time data can be matched at all other temperatures with no fitting required; our model provides a universal description of this unusua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 18 publications
1
30
0
2
Order By: Relevance
“…At the beginning of the illumination with the UV intensity pattern, the photoisomerization reaction takes place only in a few micrometers thick surface layer of the film, but later on, photobleaching of the azobenzene dye molecules allows UV light to penetrate deeper and deeper into the sample depth . The associated periodic refractive index modulation causes optical diffraction of the probe beam.…”
Section: Resultsmentioning
confidence: 99%
“…At the beginning of the illumination with the UV intensity pattern, the photoisomerization reaction takes place only in a few micrometers thick surface layer of the film, but later on, photobleaching of the azobenzene dye molecules allows UV light to penetrate deeper and deeper into the sample depth . The associated periodic refractive index modulation causes optical diffraction of the probe beam.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In these numerous efforts, azobenzene has been used as a molecular switch to convert input light energy into conformational change which subsequently generates strain in the polymeric materials. Light is potentially a "smart" stimulus that can uniquely allow for wireless (remote) spatio-temporal control of the force or shape change.…”
mentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In these numerous efforts, azobenzene has been used as a molecular switch to convert input light energy into conformational change which subsequently generates strain in the polymeric materials. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In these numerous efforts, azobenzene has been used as a molecular switch to convert input light energy into conformational change which subsequently generates strain in the polymeric materials.…”
mentioning
confidence: 99%
“…Photomechanical response.-In many previous theoretical studies, the photoinduced strain was commonly assumed to be linearly proportional to the cis volume fraction [8,11,12], or nonlinear but monotonically increasing [10,21]. However, the measured density decrease [14] ( Fig.…”
Section: -2mentioning
confidence: 99%
“…This actuation can be reversed by exposing the material to visible (VIS) light or heat, which accelerate the cis azobenzenes to fall back to the trans state. The current consensus in experimental [5,[7][8][9] and theoretical studies [10][11][12][13] is that the amplitude of the photoinduced deformation is related to the statistical building up of molecules in the cis state. However, a recent experimental study [14] has revealed that this is only one side of the story.…”
mentioning
confidence: 99%